Rabies and envenomings : a neglected public health issue : report of a consultative meeting, World Health Organization, Geneva, 10 January 2007 (World Health Organization, 2007)
This publication reports on a Consultative Meeting convened to discuss strategies for improving the quality and quantity of therapeutic antisera essential drugs for the effective treatment of suspected rabid dog bites and envenoming by snakebites and scorpion stings. Inadequacies in the efficacy safety and production of these antisera have created a major global public health crisis especially in Africa and Asia. Each year millions of people are bitten by dogs or snakes or stung by scorpions and the failure to provide antisera costs at least 150,000 lives and at least as many cases of permanent physical handicap. The solution to this crisis demands an international effort to promote transfer of technology to affected countries to improve standards through the WHO\'s prequalification scheme and to facilitate distribution of antisera and training of medical personnel in their optimal use.
Keywords: vzteklina; Bites and Stings; infekční lékařství; Immunization, Passive; Drug Industry; ekonomie, ekonomika, ekonomika zdravotnictví; antiveniny; farmacie a farmakologie; farmaceutický průmysl; Antivenins; kousnutí a bodnutí; pasivní imunizace; Rabies